The stalled revolution : is equality for women an impossible dream? - Tutchell, Eva; Edmonds, John, active 2017 (Bingley, U.K. : Emerald Publishing Limited, 2017)
100 years ago women in the UK won the vote and 50 years ago the Women's Liberation Movement began a sustained campaign for equal rights. Eva Tutchell and John Edmonds draw upon historical perspectives and contemporary interviews to convey what it felt like to be in the heart of the campaigns - the excitement, the solidarity, the suffering and the humour. The tragedy is that, after hard-won successes, the revolution has stalled and equality for women is still a distant dream. Today men are paid more and occupy nearly 80% of the most powerful jobs across society. The Stalled Revolution poses a vital question about the future: Are women ready to draw inspiration from past successes and take a third leap forward towards equality? The book's three-part approach traces clear pathways through historical successes and disappointments, teaching a new generation of campaigners how to confront the many challenges that face women in the modern world. The Stalled Revolution showcases how the wisdom from our collective struggles can help form the bedrock of a new and successful liberation campaign today.
Includes index.
Includes bibliographical references.
Keywords: Feminism -- History; Feminist criticism